ANALISIS KUALITAS SISTEM INFORMASI AKADEMIK PROGRAM SARJANA DI INSTITUT PERTANIAN BOGOR DARI PERSPEKTIF PENGGUNA (Quality Analysis Of Academic Information Systems Graduate Program In Bogor Agricultural University Of User Perspective) - Taufik Makbullah; Kudang Boro Seminar; Drajat Drajat Martianto (Jurnal Pustakawan Indonesia, 2017)
AbstractThe existance of information technology currently to higher education institution had become a necessity to support education processes. Manajemen Information Academic System (SIMAK) IPB is an aplication (software) that organize the whole academic activity processes namely compiling lectures’ schedules, re-registration through online KRS completion and academical data reports. The purpose of this study is to analyze the obstacles, analyzing the quality level of SIMAK IPB and to formulate recomendation of policy strategy to SIMAK IPB service improvement. Based on the result of SERVQUAL Gap analysis discover that performance degree of the services provide by Bogor Agricultural University was bigger than importance degree perceived by users of academic system in Bogor Agricultural University due to the SERVQUAL score valued >-0, which means the services provide by Bogor Agricultural University have already fulfill users’ expectation. The IPA resulted that in quadran A of Cartesian Diagram, based on students’ perception, there were 7 attributes which will become the main priority to be improved. Meanwhile, based on academic staffs’ perception indicated that there were 6 attributes that become the main priorityto be improved. The conclusion of this study users’ satisfaction degree to SIMAK IPB obtained from questionnaire deployment to students: average value of importance degree scored 3.34 (agree) and average value of performance degree scored 3.91 (satisfy). Meanwhile, the result obtained from questionnaire deployment among academic staff, average value of importance degree scored 3.33 (agree) and average value of performance degree scored 3.92 (satisfy) Keyword: academic information system, information system quality analysis, university system information, SIMAK